THE SWEEP ALGORITHM AND THE GENERAL LINEAR MODEL - López García, Juan José (Anales de Psicología / Annals of Psychology)
In this work we analyze some views used for teaching about estimation and fitting of complex linear models based on ordinary least squared criterion. Introducing the model comparison approach as a fundamental approach, we enfatize an alternative to teach linear models with SWEEP algorithm.